Having math equations in a report can be painful. Here are some LaTeX commands often used in scientific reports. I will try to keep this post updated.

The LaTeX rendering on this website is done by an open-source package KaTeX.

## Common Structures

LaTeX Code Output
\frac{abc}{xyz} $\frac{abc}{xyz}$
\overline{abc} $\overline{abc}$
\underline{abc} $\underline{abc}$
\overrightarrow{abc} $\overrightarrow{abc}$
\overleftarrow{abc} $\overleftarrow{abc}$
\sqrt{abc} $\sqrt{abc}$
\sqrt[n]{abc} $\sqrt[n]{abc}$
\widehat{abc} $\widehat{abc}$
\widetilde{abc} $\widetilde{abc}$
𝚏'' $f''$
\overbrace{abc} $\overbrace{abc}$
\underbrace{abc} $\underbrace{abc}$
\underbrace{x+\cdots+x}_{n\text{ times}} $\underbrace{x+\cdots+x}_{n\text{ times}}$
\frac{\partial y}{\partial x1} $\frac{\partial y}{\partial x1}$
\frac{\mathrm{d} Q}{\mathrm{d} t} $\frac{\mathrm{d} Q}{\mathrm{d} t}$
\sum^{n}_{i=1} $$\sum^{n}_{i=1}$$
\prod^{n}_{i=1} $$\prod^{n}_{i=1}$$
\lim_{x\to\infty} f(x) $$\lim_{x\to\infty} f(x)$$
\int_{a}^{b} x^2 dx $$\int_{a}^{b} x^2 dx$$

## Math Operators

Code Output
\delta $\delta$
\Delta $\Delta$
\nabla $\nabla$
\forall $\forall$
\mathbb{R} $\mathbb{R}$
\in $\in$

## Arrows and Brackets

Code Output
\leftarrow $\leftarrow$
\Leftarrow $\Leftarrow$
\rightarrow $\rightarrow$
\Rightarrow $\Rightarrow$
\leftrightarrow $\leftrightarrow$
\Leftrightarrow $\Leftrightarrow$

## Greek Letters

\alpha α \beta β \gamma γ \delta δ \epsilon ϵ \zeta ζ \eta η \theta θ \iota ι \kappa κ \lambda λ \mu μ \nu ν \xi ξ \omicron ο \pi π \rho ρ \sigma σ \tau τ \upsilon υ \phi ϕ \chi χ \psi ψ \omega ω \varepsilon ε \vartheta ϑ \varkappa ϰ \varpi ϖ \varrho ϱ \varsigma ς \varphi φ \digamma ϝ

## Sample Equations

### 1. Code

\frac{\mathrm{d}}{\mathrm{d} x}\left[|w x-y|^{2}\right]=2(w x-y) \cdot w

### 1. Output

$\frac{\mathrm{d}}{\mathrm{d} x}\left[|w x-y|^{2}\right]=2(w x-y) \cdot w$

### 2. Code

\sigma=\frac{e^z}{1+e^z}

\sigma’=\frac{e^z}{(1+e^z)^2}=\frac{e^z}{1+e^z} \cdot \frac{1}{1+e^z} =\sigma(1-\sigma)

### 2. Output

$\sigma=\frac{e^z}{1+e^z}$

$\sigma’=\frac{e^z}{(1+e^z)^2}=\frac{e^z}{1+e^z} \cdot \frac{1}{1+e^z} =\sigma(1-\sigma)$

### 3.Code

\left\{
\begin{array}{lr}
x=\dfrac{3\pi}{2}(1+2t)\cos(\dfrac{3\pi}{2}(1+2t)), &  \\
y=s, & 0\leq s\leq L,|t|\leq1.\\
z=\dfrac{3\pi}{2}(1+2t)\sin(\dfrac{3\pi}{2}(1+2t)), &
\end{array}
\right.

### 3.Output

$\left\{ \begin{array}{lr} x=\dfrac{3\pi}{2}(1+2t)\cos(\dfrac{3\pi}{2}(1+2t)), & \\ y=s, & 0\leq s\leq L,|t|\leq1.\\ z=\dfrac{3\pi}{2}(1+2t)\sin(\dfrac{3\pi}{2}(1+2t)), & \end{array} \right.$